PENGARUH PRODUCT KNOWLEDGE, ORIENTATIONS DAN CAPABILITIES TENTANG EKONOMI ISLAM TERHADAP PERILAKU TRANSAKSI EKONOMI - Mohammad Nasir; Fatmah; Ummiy Fauziyah Laili; Aris Fanani (Istithmar: Jurnal Studi Ekonomi Syariah, 2020)
Research on the Effect of Product Knowledge, Orientations and Capabilities on Islamic Economics on the Behavior of Economic Transactions aims to find out how much influence between these variables in lecturer transaction behavior. The method used in this research is associative quantitative. The number of respondents used was 57 lecturers. The sampling method of this study used a purposive sampling technique. Stages of data testing through validity and reliability, classic assumption tests, multiple linear regression tests, coefficient of determination tests, and partial T tests. The results of the partial t-statistic test showed that the product knowledge and orientation variables did not significantly influence. It can be seen by using the 0.05 significance level, the significance value of product knowledge is 0.509 with a t value of 0.665 and a significance value of orientation is t arithmetic 0.170 with a significance of 0.866. While the capabilities variable with a calculated value of t = 5.755 with a significance level of 0.000 using a significance limit of 0.05, the significance value is smaller than the 5% level and is categorized as a positive and significant effect.